Pessimism, Computer Failure, and Information Systems Development in the Public Sector. - Goldfinch, Shaun (Public Administration Review, 2007)
The majority of information systems developments are unsuccessful. The larger the development, the more likely it will be unsuccessful. Despite the persistence of this problem for decades and the expenditure of vast sums of money, computer failure has received surprisingly little attention in the public administration literature. This article outlines the problems of enthusiasm and the problems of control, as well as the overwhelming complexity, that make the failure of large developments almost inevitable. Rather than the positive view found in much of the public administration literature, the author suggests a pessimism when it comes to information systems development. Aims for information technology should be modest ones, and in many cases, the risks, uncertainties, and probability of failure mean that new investments in technology are not justified. The author argues for a public official as a recalcitrant, suspicious, and skeptical adopter of IT.